Ethylene glycol rapid methods of detection - Blevins, Lori A. (Kansas State University, 2015)
Every year thousands of domestic animals are poisoned by ethylene glycol. Exposure is normally orally, but may be dermal, and poisonings are usually accidental and not malicious. Antifreeze, overwhelmingly the source of the ethylene glycol poisoning, is responsible for over 99% of reported cases. Storage, handling and proper disposal of ethylene glycol is extremely important in limiting access to this deadly product. Ethylene glycol exposures were involved in 1737 calls made to the American Society for the Prevention of Cruelty to Animals call center between 2006 and 2011. Dogs were involved in approximately 87% of exposures and cats in 13%. There were no seasonal or breed patterns. The most common clinical signs reported were neurological and gastrointestinal for both cats and dogs. Urinary calcium oxalate crystals were reported in 28.6% of exposed cats, and 21% of dogs. Attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) was used to detect calcium oxalate crystals in wax-mounted kidneys from twenty total cases, ten of which were suspected ethylene glycol poisoning submitted to the Kansas State Veterinary Diagnostic Laboratory, and ten samples deemed negative by a pathologist using light microscopy. Pure calcium oxalate monohydrate was used as a reference, and a unique absorption peak was detected between wavenumbers 1290 cm[superscript]-1 and 1320 cm[superscript]-1. The drying of kidney tissues resulted in increased sensitivity for calcium oxalate. Crystal detection by the ATR-FTIR was compared to light microscopy. Bi-fringence of crystals allowed microscopic detection, but the ATR-FTIR specificity for the test was 100%, and sensitivity was 80% compared to traditional microscopy for ca-oxalate crystal identification. ATR-FTIR was also used to detect un-metabolized ethylene glycol in vomitus using wavenumbers 1084 cm[superscript]−1, 1039 cm[superscript]−1, and 882 cm[superscript]−1, but ethylene glycol was not detectable. Ethylene glycol concentrations in samples were much too low to be detected as ethylene glycol on the ATR-FTIR, as the limit of detection was not distinguishable until 5000 ppm using a serial dilution. These methods presented simple, reliable, quick, sensitive, stable, and highly adaptable tests for detection, diagnosis and treatment of ethylene glycol poisoning.
Keywords: ethylene glycol; Fourier Transform Infrared Spectrocopy; poisoning; Animal Diseases (0476); Animal Sciences (0475); Toxicology (0383)